TYPES AND APPROPRIATENESS: STUDENTS USAGE OF CONJUNCTIONS IN ACADEMIC WRITING - RIADI, AGUS; NATHANIA, NATHANIA; VALENTINO, YOSAFAT BARONA (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
Generally, to finish a bachelor’s degree in Indonesia, undergraduate students are required to compose a research article as a form of academic writing. One of the distinctive features of academic writing is explicitness, which shows the connection between the texts by using conjunctions to help the reader understand how the various parts of the text are related and how well they understand the ideas being presented. This paper aimed to explore the conjunction usage in the research articles written by nine students from three higher educational institutions in West Borneo. Using a content analysis sheet, this qualitative research was done by interpreting the context of the conjunctions used in students’ research articles and evaluating their compatibility with each purpose of the conjunctions by adopting the misuse pattern of conjunctions theory. The research procedure consisted of coding each sentence that contained a conjunction, categorizing the conjunctions based on the types, analyzing the conjunction, and classifying the conjunctions found into two categories, which are appropriate and inappropriate. The findings showed that the most frequent conjunctions used by the students are “because they tend to add information in order to elaborate on the ideas of the sentences.